Integration of Penman approach with complementary principle for evaporation research. Issue 19 (25th July 2018) - Han, Songjun; Tian, Fuqiang
Abstract: Natural evaporation occurs with water transportation from an unsaturated land surface into an unsaturated atmosphere. The subprocesses at the land surface and in the atmosphere are one‐sidedly emphasized in the Penman approach and the complementary principle, in which the ratio of actual evaporation to the Penman potential evaporation is expressed as a function of the wetness state of the land surface and the atmosphere, respectively. The Penman approach and complementary principle can be integrated for completely conceptualizing the evaporation process, by expressing the evaporation ratio as a function of both the land surface and atmospheric wetness. The integrated approach has the potential to increase the accuracy of evaporation estimation while reducing the burdens of parameterization.